A neuropeptide modulates sensory perception in the entomopathogenic nematode Steinernema carpocapsae - Morris, Robert (PLoS Pathog, 2017)
Entomopathogenic nematodes (EPNs) employ a sophisticated chemosensory apparatus to detect potential hosts. Understanding the molecular basis of relevant host-finding behaviours could facilitate improved EPN biocontrol approaches, and could lend insight to similar behaviours in economically important mammalian parasites. FMRFamide-like peptides are enriched and conserved across the Phylum Nematoda, and have been linked with motor and sensory function, including dispersal and aggregating behaviours in the free living nematode Caenorhabditis elegans. The RNA interference (RNAi) pathway of Steinernema carpocapsae was characterised in silico, and employed to knockdown the expression of the FMRFamide-like peptide 21 (GLGPRPLRFamide) gene (flp-21) in S. carpocapsae infective juveniles; a first instance of RNAi in this genus, and a first in an infective juvenile of any EPN species. Our data show that 5 mg/ml dsRNA and 50 mM serotonin triggers statistically significant flp-21 knockdown (-84%***) over a 48 h timecourse, which inhibits host-finding (chemosensory), dispersal, hyperactive nictation and jumping behaviours. However, whilst 1 mg/ml dsRNA and 50 mM serotonin also triggers statistically significant flp-21 knockdown (-51%**) over a 48 h timecourse, it does not trigger the null sensory phenotypes; statistically significant target knockdown can still lead to false negative results, necessitating appropriate experimental design. SPME GC-MS volatile profiles of two EPN hosts, Galleria mellonella and Tenebrio molitor reveal an array of shared and unique compounds; these differences had no impact on null flp-21 RNAi phenotypes for the behaviours assayed. Localisation of flp-21 / FLP-21 to paired anterior neurons by whole mount in situ hybridisation and immunocytochemistry corroborates the RNAi data, further suggesting a role in sensory modulation. These data can underpin efforts to study these behaviours in other economically important parasites, and could facilitate molecular approaches to EPN strain improvement for biocontrol.